2017
DOI: 10.1371/journal.pone.0179749
|View full text |Cite
|
Sign up to set email alerts
|

Immune profiles and clinical outcomes between sepsis patients with or without active cancer requiring admission to intensive care units

Abstract: BackgroundImmunoparalysis was observed in both patients with cancer and sepsis. In cancer patients, Cytotoxic T lymphocyte antigen-4 and programmed cell death protein 1/programmed death-ligand 1 axis are two key components of immunoparalysis. Several emerging therapies against these two axes gained significant clinical benefit. In severe sepsis patients, immunoparalysis was known as compensatory anti-inflammatory response syndrome and this has been suggested as an important cause of death in patients with seps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…The higher Charlson Comorbidity Index in the VAE group was due to the higher percentage of patients with cancer. As in our previous study, sepsis patients with underlying active cancer had higher baseline levels of plasma IL-10 9 . Although IL-10 levels were higher in the late VAE group than in the non-VAE group on day 1 and day 7, whether cancer patients were at risk of developing VAE for this reason needs further investigation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The higher Charlson Comorbidity Index in the VAE group was due to the higher percentage of patients with cancer. As in our previous study, sepsis patients with underlying active cancer had higher baseline levels of plasma IL-10 9 . Although IL-10 levels were higher in the late VAE group than in the non-VAE group on day 1 and day 7, whether cancer patients were at risk of developing VAE for this reason needs further investigation.…”
Section: Discussionsupporting
confidence: 80%
“…Plasma and peripheral blood mononuclear cell preparation, measurements of human leukocyte antigen D-related (HLA-DR) monocyte expression, and cytokine levels have been described in our previous studies 9 , 10 .…”
Section: Methodsmentioning
confidence: 99%
“…We are actively studying the effect of co-morbidity on the outcomes of patients with sepsis, although it is out of the scope of this study. Our previous study revealed that among patients admitted to the ICU with sepsis, those with underlying active cancer had higher baseline levels of plasma IL-10, higher trend of G-CSF and higher mortality rate than those without active cancer 30 . Our ventilator dependence risk score could help predict who will need prolonged mechanical ventilation.…”
Section: Discussionmentioning
confidence: 94%
“…We used LPS-induced inflammation in macrophages as an in vitro model of sepsis. Sepsis is a life-threatening condition, and is one of the leading causes of mortality worldwide; patients’ outcomes are dependent on their immune response [ 49 , 50 ]. Despite the efforts of medical professionals, antibiotic administration within 1 h from the time of diagnosis can be difficult [ 51 ].…”
Section: Discussionmentioning
confidence: 99%